THE PROBLEM OF STRUCTURING PEDAGOGICAL KNOWLEDGE IN THE SYSTEM PROFESSIONAL TRAINING OF THE FUTURE FOREIGN LANGUAGE TEACHERS (Pedagogy of Higher and Secondary Education, 2022)
This article observes a problem of formation person's individuality by means of course - Pedagogical Creative work